Storytelling: An Effort to Reduce Aggressiveness Madurese Pre-School Children - Yudho Bawono; Kartika Febriana; Setyaningsih Setyaningsih (Universitas Mercu Buana Jakarta, 2021)
This study aims to determine the effect of storytelling on the aggressiveness of Madurese ethnic preschool children. This study uses an experimental research approach. The experimental design used was a non-randomized pretest-posttest control group design. The research location is a Kindergarten in Bangkalan, with 20 preschool children in grade A and B as subjects. This study uses a measurement instrument in the form of an Aggressiveness Scale which is filled in based on observations and self-reports of children from parents. The collected data were tested using the non-parametric difference test, Wilcoxon. The results of this study were viewed from the aspect of aggressive behavior, namely: 1) physical aggression; 2) Verbal aggressive; and 3) Passive aggression. From the test results it was found that the experimental group experienced a decline and the untreated control group did not experience a decrease, so it can be said that the hypothesis in this study was accepted. Thus it can be concluded that storytelling can reduce the aggressiveness of Madurese ethnic preschoolers